Correlation between 18-fluorodeoxyglucose accumulation in large vessels and serological markers of inflammation in polymyalgia rheumatica: a quantitative PET study. Issue 7 (11th June 2004) - Moosig, F; Czech, N; Mehl, C; Henze, E; Zeuner, R A; Kneba, M; Schröder, J O
Abstract : Objective: To quantify 18-fluorodeoxyglucose (FDG) accumulation in large vessels in patients with polymyalgia rheumatica by positron emission tomography (PET), and to compare these data with serological markers of inflammation. Methods: 13 untreated patients with active polymyalgia rheumatica underwent FDG positron emission tomography; eight were analysed in a second PET when in clinical remission. Six patients with other highly inflammatory conditions served as controls. For quantitative analysis, FDG uptake over nine defined vascular regions, divided by an individual background value, was expressed as a region of interest (ROI) index. These data were compared with the clinical status of the patient and with erythrocyte sedimentation rate (ESR), C reactive protein, haemoglobin, and platelet and leucocyte counts. Results: By visual evaluation, 12 of the 13 patients showed an increased tracer uptake of the aorta or its major branches. By quantitative analysis, FDG uptake was significantly increased in polymyalgia rheumatica. In patients with active disease, the mean ROI index for all vascular regions exceeded that of controls by 70% (mean (SD): 1.58 (0.37) v 0.93 (0.12); p<0.001). In the eight patients who underwent follow up PET, the index declined substantially. In active polymyalgia rheumatica, FDG uptake was significantly correlated with C reactive protein ( r  = 0.8), ESR ( r  = 0.79), and platelet counts ( r  = 0.68). Conclusions: The observed FDG accumulation in the aorta and its branches and a strong correlation between tracer uptake and markers of inflammation is suggestive of large vessel arteritis. Quantitative ROI analysis appears to be a sensitive tool for detecting such inflammation.